2002
DOI: 10.1093/cercor/12.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and Temporal Processing in Human Auditory Cortex

Abstract: Hierarchical processing suggests that spectrally and temporally complex stimuli will evoke more activation than do simple stimuli, particularly in non-primary auditory fields. This hypothesis was tested using two tones, a single frequency tone and a harmonic tone, that were either static or frequency modulated to create four stimuli. We interpret the location of differences in activation by drawing comparisons between fMRI and human cytoarchitectonic data, reported in the same brain space. Harmonic tones produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
91
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(112 citation statements)
references
References 39 publications
19
91
2
Order By: Relevance
“…If we understand the cerebral cortex as a self-organizing network, it is more likely that at higher processing levels, beyond the subcortical pathways and primary sensory areas, representations develop for combinations of features that frequently occur together. Previous neurophysiological (8,11) and human neuroimaging studies (43,44) generally suggest that nonprimary regions, including PT/posterior STG, process progressively more complex sounds than the primary "core" regions of auditory cortex. These observations are in line with a previous MEG study (45) that systematically compared activations to individual and combined 3D sound features, and showed that ILD alone is not sufficient for producing direction-specific activations at the cortical level.…”
Section: Discussionmentioning
confidence: 99%
“…If we understand the cerebral cortex as a self-organizing network, it is more likely that at higher processing levels, beyond the subcortical pathways and primary sensory areas, representations develop for combinations of features that frequently occur together. Previous neurophysiological (8,11) and human neuroimaging studies (43,44) generally suggest that nonprimary regions, including PT/posterior STG, process progressively more complex sounds than the primary "core" regions of auditory cortex. These observations are in line with a previous MEG study (45) that systematically compared activations to individual and combined 3D sound features, and showed that ILD alone is not sufficient for producing direction-specific activations at the cortical level.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced activity in the fusiform gyrus during face perception has been observed in several autism studies (Hubl et al 2003;Pierce et al 2001;Schultz et al 2000), including a single case study (Grelotti et al 2005), with additional reports of reduced fusiform activity related to the processing of emotional facial expressions (Critchley et al 2000;Hall et al 2002;Piggot et al 2004). Interestingly however, two studies of face perception in autism (Hadjikhani et al 2004;Pierce et al 2004) found normal levels of activity in the fusiform gyrus.…”
Section: Functional Brain Organizationmentioning
confidence: 91%
“…An equally plausible hypothesis concerning spatial separation of local and global auditory processing is that local information might be preferentially processed in ventral areas and global information in more dorsal areas. Human auditory cortex, like visual cortex, is functionally organized in a hierarchical manner such that core areas are activated by simple stimuli (e.g., pure tones) whereas belt and parabelt areas preferentially respond to more complex sounds (Binder et al, 1997;Hall et al, 2002;Price et al, 1996;Wessinger et al, 2001). Evidence that corticocortical connections from different belt and parabelt areas diverge into a primarily anterior and a primarily posterior stream (Kaas, Hackett, & Tramo, 1999;Romanski et al, 1999) has been used to argue that there are two major functional divisions of auditory processing beyond auditory cortex (Rauschecker, 1998;Rauschecker, Tian, & Hauser, 1995).…”
Section: Lateralizationmentioning
confidence: 99%